Pop's Bridge - Bunting, Eve. (New York Harcourt, Inc., 2006)
Robert and his friend Charlie are proud of their fathers who are working on the construction of San Francisco's Golden Gate Bridge.
1 - 6
Keywords: Golden Gate Bridge (San Francisco, CA) - Fiction; Bridges - Design and construction - Fiction; Fathers - Fiction; San Francisco, CA - History - 20th Century - Fiction